2022
DOI: 10.1002/bies.202200109
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin as an adrenocorticotropic hormone: Prolactin signalling is a conserved key regulator of sexually dimorphic adrenal gland function in health and disease

Abstract: A large number of previous reports described an effect of the pituitary hormone prolactin (PRL) on steroid hormone production by the adrenal cortex. However, those studies remained anecdotal and were never converted into a conceptual and mechanistic framework, let alone being translated into clinical care. In the light of our recently published landmark study where we described PRL signalling as a pivotal regulator of the sexually dimorphic adrenal phenotype in mouse and of adrenal androgen production in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 166 publications
0
3
0
Order By: Relevance
“…The distribution of biochemical parameters of the patients according to their importance for NSSI suggests that the anterior pituitary hormones (ACTH, prolactin, TSH) may be tightly involved in its development (Figure 1b), with ACTH playing the leading role. Previously, it was shown that the level of prolactin, vulnerable to the influence of different stressors, has a regulatory effect on the adrenal glands, acting as a synergist of ACTH, and, accordingly, modifying the stress response [49]. These findings suggest that the development of NSSI in patients with NPMD may be associated with HPA axis dysregulation at the pituitary level.…”
Section: Discussionmentioning
confidence: 90%
“…The distribution of biochemical parameters of the patients according to their importance for NSSI suggests that the anterior pituitary hormones (ACTH, prolactin, TSH) may be tightly involved in its development (Figure 1b), with ACTH playing the leading role. Previously, it was shown that the level of prolactin, vulnerable to the influence of different stressors, has a regulatory effect on the adrenal glands, acting as a synergist of ACTH, and, accordingly, modifying the stress response [49]. These findings suggest that the development of NSSI in patients with NPMD may be associated with HPA axis dysregulation at the pituitary level.…”
Section: Discussionmentioning
confidence: 90%
“…These data beg further investigation of PRL/PRLR action in adrenal function, steroidogenesis, and their implications in states of stress, including the mechanisms by which stress induces hyperprolactinemia 149 . Indeed, there is a purported role for PRL in mediating the sexually dimorphic response to chronic stress 150 …”
Section: Metabolic Targetsmentioning
confidence: 92%
“…149 Indeed, there is a purported role for PRL in mediating the sexually dimorphic response to chronic stress. 150…”
Section: Adrenal Glandsmentioning
confidence: 99%